2020
DOI: 10.1021/acsabm.9b01242
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Conjugated Oligomer for Effective Killing of Bacterial through Combination of Photodynamic and Photothermal Treatment

Abstract: In recent years, phototherapeutic strategies including photodynamic therapy (PDT) and photothermal treatment (PTT) have attracted extensive interest in biological and medical applications. To achieve high efficiency in therapy, it is crucial to develop promising agents possessing synergistic PDT and PTT effects, especially those triggered by single-wavelength near-infrared (NIR) light. Herein, a low-bandgap fluorene-based conjugated oligomer OF-Green-N with a donor−acceptor−donor (D−A−D) structure was synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…8,9 In the last few years, photosensitizers (PS) have been broadly used in antibacterial photodynamic therapy (PDT) because of the high molar extinction coefficient, less toxicity, and good biocompatibility. 10,11 Some reports on their photocatalytic activity are also present. 12 They can generate reactive oxygen species (ROS) from neighboring water and oxygen molecules upon excitation.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In the last few years, photosensitizers (PS) have been broadly used in antibacterial photodynamic therapy (PDT) because of the high molar extinction coefficient, less toxicity, and good biocompatibility. 10,11 Some reports on their photocatalytic activity are also present. 12 They can generate reactive oxygen species (ROS) from neighboring water and oxygen molecules upon excitation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, the oligomer, OF GREEN N, has shown an enhanced photothermal efficiency of 37.7%. The OF GREEN N oligomer displayed enhanced antibacterial activity against S. aureus under NIR laser irradiation [ 113 ]. Pegylated and thiolated (PEG-SH) gold nanorods (AuNRs) conjugated with a phospholipid (DSPE-AuNR-PEG-SH) and cholesterol (Chol-AuNR-PEG-SH) exhibited an antibacterial effect.…”
Section: Polymer-based Nanomaterialsmentioning
confidence: 99%
“…In this regard, Romero et al, 2020 showed the ability of GO as an antimicrobial agent to eliminate E. coli and S. aureus bacteria through the combination of Photodynamic Therapy (PDT) and Photothermic Therapy (PTT) [9]. Peng et al, 2020 present a conjugated oligomer with antibacterial capacity to eliminate E. coli by PDT / PTT [10]. Xu et al, 2019 showed that nanocomposites based on Graphene and carbon nanotubes are capable of eliminating bacterial loads from Cyanobacteria, E. coli, S. aureus, Pseudomonas aeruginosa, Bacillus subtilis, Pseudomonas putida and Rhodococcus spp, based on the combination of PDT and PTT [11].…”
Section: Introductionmentioning
confidence: 99%